2020
DOI: 10.1177/1049909120959057
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Applications for Advance Care Planning: A Comprehensive Review of Features, Quality, Content, and Readability

Abstract: Mobile applications that facilitate each stage of the advance care planning process (i.e., obtaining knowledge, contemplating options, and acting on decisions) may be one effective way to support patient-centered care and patient autonomy. The purpose of the current review was to identify and evaluate advance care planning mobile applications for patients. Our specific aim was to examine app features, design quality, content, and readability. We searched the Apple iOS and Google Play stores using keywords deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The app Accordons-nous obtained high scores on readability (overall score of 87.4 on the Scolarius test, corresponding to elementary school level). This is one of the best scores compared with other similar apps internationally [ 21 ]. However, the language difficulty varies across different pages of the app.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The app Accordons-nous obtained high scores on readability (overall score of 87.4 on the Scolarius test, corresponding to elementary school level). This is one of the best scores compared with other similar apps internationally [ 21 ]. However, the language difficulty varies across different pages of the app.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile apps for ACP are available in some countries. Their potential is recognized; however, existing products have limited features and operate mostly in English only [ 21 , 22 ]. We did not find comparable tools available in French.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] For example, while there has been an exponential increase in the number of eHealth tools, the quality found in usability testing has not increased at an equivalent rate. [14][15][16] Furthermore, in a recent review of the feasibility of 11 web-based ACP eHealth tools, the authors concluded that there was insufficient evidence to recommend use by individuals with limited health or computer literacy due to poor design quality. 16 In contrast, by adhering to these eHealth lessons, PREPARE has been shown to be efficacious and feasible among diverse English and Spanish-speaking older adults.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important for those experiencing systemic patterns of disadvantage, such as non-English speaking older adults and those with limited health and computer literacy. 3,12,13 Although some feasibility reviews have been conducted of web-based and mobile applications, [14][15][16][17] and online resources are available, [18][19][20] practical guidance for the development of eHealth tools for diverse older adults does not yet exist in the geriatrics literature. Therefore, the goal of this article is to provide guidance for the development and refinement of eHealth tools for diverse, older populations and provide pragmatic examples from an evidenced-based eHealth tool called PREPARE for Your Care (www.…”
Section: Introductionmentioning
confidence: 99%